Poetry, politics, and the law in modern Ireland - Hanna, Adam, 1980- (Irish studies (Syracuse, N.Y.), 2022)
"This manuscript examines poetry in post-Independence Ireland in the context of legal developments and controversies, and brings to light the importance of these things in shaping the country's literature"--